Quantifying the educational benefit of additional cataract surgery cases in ophthalmology residency. Issue 11 (November 2020) - Liebman, Daniel L.; McKay, Kenneth Matthew; Haviland, Miriam J.; Moustafa, Giannis A.; Borkar, Durga S.; Kloek, Carolyn E.
Abstract : Residents follow heterogenous paths to competency in performing cataract surgery. Most seem to derive educational benefit primarily from their first 150 cataract cases, with possible diminishing educational return-on-invested-time thereafter. Abstract : Purpose: To quantify the resident learning curve for cataract surgery using operative time as an indicator of surgical competency, to identify the case threshold at which marginal additional educational benefit became equivocal, and to characterize heterogeneity in residents' pathways to surgical competency. Setting: Academic medical center. Design: Large-scale retrospective consecutive case series. Methods: All cataract surgery cases performed by resident physicians as primary surgeon at Massachusetts Eye and Ear from July 1, 2010, through June 30, 2015, were reviewed. Data were abstracted from Accreditation Council for Graduate Medical Education case logs and operative time measurements. A linear mixed-methods analysis was conducted to model changes in residents' cataract surgery operative times as a function of sequential case number, with resident identity included as a random effect in the model to normalize between-resident variability. Results: A total of 2096 cases were analyzed. A marked progressive decrease in operative time was noted for resident cases 1 to 39 (mean change −0.17 minutes per additional case, 95% CI, −0.21 to −0.12; P < .001). A modest, steady reduction in operative time was subsequently noted for case numbers 40 to 149 (mean change −0.05 minutes per additional case, 95% CI, −0.07 to −0.04; P < .001). No statistically significant improvement was found in operative times beyond the 150th case. Conclusions: Residents derived educational benefit from performing a greater number of cataract procedures than current minimum requirements. However, cases far in excess of this threshold might have diminishing educational return in residency. Educational resources currently used for these cases might be more appropriately devoted to other training priorities.